Wolves in the Toruń Basin - Sewerniak, Piotr (Uniwersytet Mikołaja Kopernika w Toruniu, 2010)
The present wolf population of the Toruń Basin is one of the very few that exist in the central and the western part of Poland. Wolves populated the region at the turn of the 20th and 21st centuries, and at least since 2004 they reproduced in the forests on both sides of the Vistula River. The population from the Toruń Basin is probably an important source of wolves that colonize Western Poland and spread to Western Europe. However, the human pressure on the environment is continuously increasing in the Toruń Basin, therefore the future stability of the existence of wolves in the region is uncertain. The aim of the paper is to present the main data on the occurrence of wolves in the Toruń Basin, together with the main human threats to the wolf population in this region.